Conflict and Competition: Agon in Western Greece Selected Essays from the 2019 Symposium on the Heritage of Western Greece - Reid, Heather L. (Heritage of Western Greece, 2020)
In 2004, the city of Athens hosted the Olympiakoi Agōnes, the Olympic Games. But the word 'games' almost trivializes the ancient concept of agōn, which transcends sport, drama, war, and even philosophical debate. The agōn deemed characteristic of ancient Greek culture has roots in the eris (strife) illustrated in Homer and Hesiod and debated in the metaphysics of Heraclitus and Empedocles. It reverberates throughout philosophy, drama, history, poetry, art, and even the 19th century reception of Greek culture. This volume considers agōn from a variety of disciplinary perspectives, with a special emphasis on Western Greece - the ancient Hellenic cities of Sicily and Southern Italy. Authors discussed include Heraclitus, Pythagoras, Empedocles, Euripides, Thucydides, Plato, Aristotle, Theocritus, Callimachus, Diodorus, Porphyry, Nietzsche, and Burckhardt.